Energy Saving For Mobile Users Using Cloud Computing Via S3 - Venkateswarlu, K; Lakshmi, M.S; Kumar, S.P (International Journal of Computer Sciences and Engineering, 2014)
With a rise in usage of mobile devices it`s continuously expected that a mobile device perform the execution of all applications the approach a desktop device do. Mobile devices became associate integral a part of somebody`s life. However, with restricted process power, memory & battery time period of mobile phones it becomes tough to execute computationally intensive applications like image process. Computation offloading provides a way to save lots of energy within which a number of the applying computer code parts are often offloaded from mobile device to run on a distant server. Offloading the computation from mobile devices into cloud can end in extended battery time period, improved knowledge storage capability and process power. Offloading the computation from mobile devices (low in resources) into cloud (resourceful machine) solves the matter. This analysis presents service primarily {based} offloading mechanism that permits execution of multiple computations and repair based access mechanism for higher purpose. Here to perform multiple computations, multiple services square measure run each at consumer aspect (mobile devices) and server aspect (Cloud). The cloud modules contains of Image clump, Image retrieval and image search service whereas robot module encompass Image storage and management, Login and registration ,Image search and image transfer service. The execution of multiple services can guarantee quicker execution and increase in battery time period.